Hair matters : beauty, power, and Black women's consciousness - Banks, Ingrid, 1966- (New York University Press, 2000)
"Long hair in the 60s, Afros in the early 70s, bobs in the 80s, fuschia in the 90s. Hair is one of the first attributes to catch our eye, not only because it reflects perceptions of attractiveness or unattractiveness, but also because it conveys important political, cultural, and social meanings, particularly in relation to group identity. Given that mainstream images of beauty do not privilege dark skin and tightly coiled hair, African American women's experience provides a starkly different perspective on the meaning of hair in social identity."--National Women's Studies Association Journal